Nicoya earthquake rupture anticipated by geodetic measurement of the locked plate interface - Protti, Marino (2014)
The Nicoya Peninsula in Costa Rica is one of the few places on Earth where the seismically active plate interface of a subduction zone is directly overlaid by land rather than ocean. At this plate interface, large megathrust earthquakes with magnitudes greater than 7 occur approximately every 50 years. Such quakes occurred in 1853, 1900 and 1950, so another large earthquake had been anticipated1, 2. Land-based Global Positioning System3, 4 (GPS) and seismic5, 6, 7 measurements revealed a region where the plate interface was locked and hence accumulated seismic strain that could be released in future earthquakes. On 5 September 2012, the long-anticipated Nicoya earthquake occurred in the heart of the previously identified locked patch. Here we report observations of coseismic deformation from GPS and geomorphic data along the Nicoya Peninsula and show that the magnitude 7.6 Nicoya earthquake ruptured the lateral and down-dip extent of the previously locked region of the plate interface. We also identify a previously locked part of the plate interface, located immediately offshore, that may not have slipped during the 2012 earthquake, where monitoring should continue. By pairing observations of the spatial extent of interseismic locking and subsequent coseismic rupture, we demonstrate the use of detailed near-field geodetic investigations during the late interseismic period for identifying future earthquake potential.